Identification of Potential Sites for Future Lake Formation and Expansion of Existing Lakes in Glaciers of Chandra Basin, Western Himalayas, India - Pandit, Ankur; Ramsankaran, RAAJ (Frontiers in Earth Science, 2020)
Disappearance of mountain glaciers and formation/expansion of glacial lakes are amongst the most distinguishable and dynamic impacts of climate warming in the Himalayas. The present research focuses on the identification of potential sites for future lake formation in the selected sixty-five study glaciers of Chandra basin located in the western Himalayas. The study adopted stress-driven, physics-based GlabTop2_IITB model to obtain the ice-thickness distribution, which was then used to extract the bedrock topography. Based on the overdeepenings determined from the derived glacier bed topographies, a total of 350 potential future glacial lakes (PFGLs) were identified, and a detailed high resolution database of these lakes was generated. The identified PFGLs were found to occupy an area of 49.56 km2, corresponding to 8.4% of the current total area of the sixty-five study glaciers (591 km2). The total storage volume of these PFGLs was estimated as 1.08 ± 0.16 km3. In our study region, 20 PFGLs were identified as potentially hazardous in the event of Glacial Lake Outburst Flood (GLOF) occurrence, and their combined storage volume was found to be more than 106 m3), which calls for continuous monitoring of the glaciers in this region.